The Differences in Characteristics of Preeclampsia Before and During The COVID-19 Pandemic: Systematic Review - Kusuma, Rahayu; Aditiawarman, Aditiawarman; Atika, Atika (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: The COVID-19 pandemic has entered Indonesia since 2020 and has become a global pandemic. In the pre-pandemic period, Preeclampsia was one of the main causes of death of pregnant women in Indonesia. During the COVID-19 pandemic, the mortality rate of pregnant women and childbirth due to preeclampsia has the possibility of an increase. The cause of preeclampsia in pregnant women is not yet known. Early detection of risk factors and early treatment of preeclampsia are not carried out quickly and appropriately due to social restrictions due to the pandemic. Subject and Method: This study is a systematic review literature review conducted on selected databases (PubMed, Science Direcet, Unair Repository) with a publication year between 2017 and 2022. Literature uses Indonesian and English. The literature included was literature with cohort, cross sectional, and case control methods. The quality assessment of the literature was carried out using the EPHPP (Effective Public Health Practice Project). Results: There were no significant differences in Preeclampsia characteristics i.e. age at pregnancy, parity, and BMI in both periods before and during the COVID-19 pandemic. However, differences were found that only existed in the period during the COVID-19 pandemic, namely comorbid diseases and previous history of preeclampsia Conclusions: In the period before and during the COVID-19 pandemic, pregnant women with preeclampsia did not show differences in outcomes in characteristics, but in the history of comorbid diseases and previous history of preeclampsia.